PREVALENCE OF SEPTATION AND SYMMETRY OF SPHENOID SINUS AND NASAL SEPTAL DEVIATION IN MULTISLICE COMPUTED TOMOGRAPHY - Newman, Nadya Imani; Mendonça, Diego Santiago de; Silva, Paulo Goberlânio de Barros; Ribeiro, Esther Carneiro; Costa, Fábio Wildson Gurgel (Brazilian Journal of Case Reports, 2023)
The sphenoid sinuses (SS) are pneumatic spaces located in the diaphysis of the sphenoid bone. The morphology of the SS is characterized by great diversity. One such being the presence of septa; which may vary in number and be complete or incomplete. In the present study, we investigated: total number of septa present and whether there is a relationship between septation, symmetry and nasal septal deviation (SD) using multidetector computed tomography (MDCT) in adults from the state of Para and Ceara. A retrospective cross-sectional study was carried out with images of patients who did not present any pathology in the SSs between the ages of 18-49 years. A total of 121 images were evaluated (59 females and 62 males) in the axial plane using the ITK-SNAP software version 3.6.0. Results were recorded by age and gender and revealed that in both males (100%) and females (98.3%%); SS was detected as having at least one complete septum. SD was present in 45.5% of patients and asymmetry was detected in 77.7%. In conclusion the present study verified that the diversity of anatomical variations present is considerable; therefore, its tomographic evaluation may aid in surgical planning or forensic identification, however more specific studies within different populations are necessary.